Heroes in Miniature: Wandering Images of Thule between Greenland and Denmark (1935-1936) - Hemkendreis, Anne (Nordlit, 2022)
This paper examines the five different Thule postal stamps which circulated from 1935 to 1936 between the trading post of Thule (which is the Danish name for the settlement of Uummannaq in Northwest Greenland, today Thule Air Base) and the Cape York post office in Copenhagen. The images on the stamps not only concentrate and visualize the complex colonial history between Greenland and Denmark. Instead, they also dynamize and preserve historical power relations by making them physically and visually tangible to this day. The stamps bear witness to infra-structures of cultural exchange, which were strongly controlled by the Danish side. They are often overlooked testimonies of everyday communication and mark colonial relations as ongoing and still powerful forces. What is more, the stamps provide their own agency as cultural-creating forces which sheds a new light to the history of Western modernization and its heritage.
Keywords: is; Knud Rasmussen; Thule; Frimerker; Vandrende bilder; Grønland